Rasch Model Analysis of Algebraic Numeracy Literacy Items Using Winsteps - Rifqi Hidayat; Turmudi Turmudi; Jarnawi Jarnawi; Elah Nurlaelah (MASI Mandiri Edukasi, 2025)
The limited availability of valid and reliable numeracy literacy test instruments, particularly in the algebra domain, for junior high school students in preparation for the Minimum Competency Assessment exam makes this research important to conduct. This study aims to describe the quality of a numeracy literacy test instrument in the algebra domain for junior high school students. It is a quantitative study with a descriptive approach. This method is used to describe the quality of the numeracy literacy test instrument in the algebra domain, which was developed based on Rasch modeling. The research procedure comprises three main phases: item development, limited trial testing with 8th-grade students, and item quality analysis using the Rasch model analysis with the Winsteps software. The developed numeracy literacy test instrument consists of 12 essay questions. The instrument was then used to collect quantitative data from 34 8th-grade students selected as research respondents through purposive sampling. The results indicate that one item is categorized as invalid (requiring revision), while the remaining items are deemed valid. The reliability index is 0.80, which falls into the ideal category. The analysis of item difficulty levels reveals that one item is categorized as difficult, nine items as moderate, and two items as easy. Overall, the developed algebra numeracy literacy instrument meets the criteria of Rasch modelling, although one item requires revision. Teachers can use this instrument as an assessment tool to evaluate students' algebraic numeracy literacy skills in junior high school. This instrument can also serve as a model for developing numeracy literacy test instruments in other domains.